Religious freedom, LGBT rights, and the prospects for common ground - Eskridge, William N. 1951-; Wilson, Robin Fretwell (Cambridge Cambridge University Press, 2018)
The rights of lesbian, gay, bisexual, and transgender persons (LGBT) are strongly contested by certain faith communities, and this confrontation has become increasingly pronounced following the adjudication of a number of legal cases. As the strident arguments of both sides enter a heated political arena, it brings forward the deeply contested question of whether there is any possibility of both communities' contested positions being reconciled under the same law. This volume assembles impactful voices from the faith, LGBT advocacy, legal, and academic communities - from the Human Rights Campaign and ACLU to the National Association of Evangelicals and Catholic and LDS churches. The contributors offer a 360-degree view of culture-war conflicts around faith and sexuality - from Obergefell to Masterpiece Cakeshop - and explore whether communities with such profound differences in belief are able to reach mutually acceptable solutions in order to both live with integrity.
Title from publisher's bibliographic system (viewed on 15 Nov 2018)
Keywords: Civil Rights -- Religious aspects; Freedom Of Religion -- United States; Sexual minorities -- Civil rights -- United States; Discrimination -- Religious aspects; Freedom of religion ; United States; Sexual minorities ; Civil rights ; United States; Discrimination ; Religious aspects; Civil rights ; Religious aspects; Konferenzschrift